Constraints to effective use of learning technology among commerce students at a historically disadvantaged rural university in South Africa - Eposi, Elsie Mbua; Matarirano, Obert (Edelweiss Applied Science and Technology, 2025)
Technology is vital in education, but students often struggle to use learning tools effectively. This study aimed to identify the constraints on the effective use of learning technology by commerce students at a rural South African university and propose practical solutions to these challenges. The study was grounded in the extended Technological Acceptance Model (eTAM) and employed a quantitative approach utilizing a descriptive research design. Data were collected through a self-administered questionnaire and analyzed using descriptive statistics with critical analysis techniques. The analysis of the student survey revealed significant constraints affecting the success of commerce students, including economic limitations, outdated resources, inadequate technical infrastructure, and a pressing need for frameworks that promote innovative and inclusive learning environments. Based on the findings, institutions should prioritize advanced strategies that foster inclusion and accessibility, such as offering lower costs for learning materials, ensuring reliable internet access, providing technical support, and implementing continuous improvements. These measures will help facilitate equitable access to technology, enhance learning opportunities, and improve student experiences, ultimately leading to better academic performance.